Cadherin 23 is a component of the tip link in hair-cell stereocilia: letters to nature - Siemens, Jan; Lillo, Concepcion; Dumont, Rachel A.; Reynolds, Anna; Williams, David S.; Gillespie, Peter G.; Müller, Ulrich (Nature, 2004)
Mechanoelectrical transduction, the conversion of mechanical force into electrochemical signals, underlies a range of sensory phenomena, including touch, hearing and balance. Hair cells of the vertebrate inner ear are specialized mechanosensors that transduce mechanical forces arising from sound waves and head movement to provide our senses of hearing and balance1,2; however, the mechanotransduction channel of hair cells and the molecules that regulate channel activity have remained elusive. One molecule that might participate in mechanoelectrical transduction is cadherin 23 (CDH23), as mutations in its gene cause deafness and age-related hearing loss3,4,5,6. Furthermore, CDH23 is large enough to be the tip link, the extracellular filament proposed to gate the mechanotransduction channel7. Here we show that antibodies against CDH23 label the tip link, and that CDH23 has biochemical properties similar to those of the tip link. Moreover, CDH23 forms a complex with myosin-1c, the only known component of the mechanotransduction apparatus8, suggesting that CDH23 and myosin-1c cooperate to regulate the activity of mechanically gated ion channels in hair cells.